Design and Performance of 8Slot-12Pole Permanent Magnet Flux Switching Machines for Electric Bicycle Application - Laili Iwani Jusoh; Erwan Sulaiman; Rajesh Kumar; Fatihah Shafiqah Bahrim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents a new design and performance of single phase permanent magnet flux-switching machine (PMFSM) for electric bicycle application. 8Slot-12Pole design machine were choose by analyzing the highest power density value. All active parts such as permanent magnet and armature coil are located on the stator, while the rotor part consists of only single piece iron. PMFSM have a great advantage with robust rotor structure that make it much higher power and applicable for EV application compared to SRM and IPMSM. The design, operating principles, characteristics of torque, and power of this new topology are investigated by JMAG-Designer via a 2D-FEA. Size of motor and volume of PM is designed at 75mm and 80g, respectively. Based on the investigation, it can be concluded that the proposed topology of single phase 8Slot 12Pole PMFSM achieved the target of highest performance of power density, approximately at 0.113W/mm3 with reduced permanent magnet and size of design motor. Due to the low torque performance of this initial design, further works is ongoing to improve the torque performance. In future work, outer rotor PMFSM structure design will be presented and compared with the “Deterministic Optimization Method” to improve the initial design.